Muslims responses to pandemics: lessons from the best generation - Che Mohamad, Che Anuar; Shahar, Mohammad Arif; Tahir, Mohd Faiz; Syed Abd Hamid, Syed Abdul Khaliq (Kulliyyah of Medicine,IIUM, 2020)
The world is currently suffering from another episode of respiratory disease pandemic as Coronavirus Disease 2019 (COVID-19) spares no continent. The disease which is caused by the virus SARS-CoV-2, has so far claimed many lives in multiple countries, including Muslim majority nations like Malaysia and Saudi Arabia. The situation has become a significant public health concern with several measures being carried out in an attempt to break the chain of the virus transmission. These include the introduction of movement control order and total lock down across the world. The closure of places of worship including mosques have raised concerns and inconvenience to Muslims. Pandemics are not unprecedented in the history of mankind as several documented outbreaks like the plague pandemic in the mid fourteenth century also known as ‘the Black Death’, caused a demographic decline in both Muslim and Christian countries which led to millions of lives loss worldwide. We attempt to identify the parallels between the current COVID-19 pandemic with the experiences of previous Muslim generations, and draw lessons on general and practical responses to pandemics with special reference to the generation of the Prophet’s companion.